The Structural Relationship among Students’ Perceptions of Sales-Related Skills, Sales Careers, and Views of Others and the Intention to Pursue Sales Careers in Malaysia: The Mediating Effect of Feelings towards Selling - Nor Asiah Omar; Nadzirah Rosli; Syed Shah Alam; Abu Hanifah Ayob; Muhamad Azrin Nazri (UKM Press, 2024)
Indexed by Scopus/MyCite